Assessment of Complications According to the Clavien-Dindo Classification After Distal Pancreatectomy - Casadei, Riccardo; Ricci, Claudio; Pezzilli, Raffaele; Calculli, Lucia; D’Ambra, Marielda; Taffurelli, Giovanni; Minni, Francesco (JOP. Journal of the Pancreas, 2011)
Context The absence of a definition and a widely accepted ranking system to classify surgical complications has hampered proper interpretation of the surgical outcome. Patients Sixty-one patients undergoing distal pancreatectomy. Main outcome measures The complications were classified according to the Clavien-Dindo classification; each grade was evaluated regarding the length of the postoperative stay and was compared to the most important complications. Results Thirty (49.2%) patients had no complications; out of the thirty-one (50.8%) patients with complications, 9 (14.5%) had grade I, 15 (24.6%) had grade II, 6 (9.8%) had grade III, and 1 (1.6%) had grade IV. There were no postoperative deaths (grade V). A progressive increase in the length of hospitalization from patients with no complications to those having grade IV (P<0.001) was noted. Postoperative pancreatic fistula and postpancreatectomy hemorrhage rates did not significantly increase from Clavien-Dindo grade I to grade IV (P=0.118 and P=0.226, respectively). The severity of a postpancreatectomy hemorrhage, instead, was positively related to the grade of the Clavien-Dindo classification (P=0.049) while postoperative pancreatic fistula resulted near the significant value (P=0.058). Conclusions The Clavien-Dindo classification is a simple way of reporting all complications following distal pancreatectomy. It allows us to distinguish a normal postoperative course from any deviation and the severity of complications and it may be useful for comparing postoperative morbidity between different pancreatic centers. Image: Relationship between the length of the postoperative stay and the Clavien-Dindo classification.